After Three Years : Discerning Signs of the Time in the Age of Trump - Haynes, Stephen R. 1958- (2024)
Many things changed in America during the first three years of the Trump presidency (2017-2019). What did not change was the proclivity of Americans to view social and political developments through the lens of Dietrich Bonhoeffer’s life and writings. In letters to the editor of local newspapers, op-ed pieces, blog posts, teaching videos, book reviews, podcasts and magazine articles, Americans in every part of the country and from across the political spectrum used Bonhoeffer’s actions, words, and purported words to bolster their rhetorical cases. In the process they were deterred neither by a weak grasp of the details of Bonhoeffer’s biography nor by an obligation to consult primary sources. After three years of the Trump presidency, there was every indication that Bonhoeffer would continue to play an outsized role in American political discourse.
Keywords: Abortion; Dietrich Bonhoeffer; Donald Trump; Eric Metaxas; Refugees; Abortion; Refugees